Survival in patients with CKD 3–5 after 12 months of exercise training – a post-hoc analysis of the RENEXC trial - Sara Denguir; Matthias Hellberg; Martin Almquist; Naomi Clyne (BMC Nephrology)
Abstract Background Physical performance is low and physical activity declines in people with chronic kidney disease (CKD). Both factors are associated with decreased survival. Our hypothesis was that improved physical performance after 12 months of exercise training would result in better survival in patients with CKD stages 3 to 5 not on kidney replacement therapy (KRT). Our aims in this study were to investigate the survival effects of (1) baseline physical performance and (2) physical performance after 12 months of exercise training. Methods This is a post-hoc analysis of the RENEXC trial, a randomized controlled study comparing 12 months of strength- and balance training both in combination with aerobic training. Both groups improved physical performance with no between group differences. Patients were categorized into five groups: improved ≥ 5%, unchanged, deteriorated ≥ 5%, non-completers, missing data. Univariate and multivariate Cox regression analyses were used and adjusted for age, sex, comorbidity, time on dialysis and time with a kidney transplant. Results 151 patients participated, mean age 66 ± 14 years, 65% men, eGFR 22.5 ± 8.2 ml/min/1.73m2, average follow-up 60 months. Multivariate analyses The baseline 6-minute walk test (6MWT) (HR 0.996; 95% CI [0.993–0.998]) and 30-second sit-to-stand (30s-STS) (HR 0.94 CI [0.89–1.0]) were positively associated with survival. After 12 months of exercise improved handgrip strength (HGS) right (HR 2.66; 95% CI [1.07–6.59]) was associated with better survival compared with deterioration. Improvement compared with noncompletion was associated with better survival (6MWT (HR 2.88; 95% CI [1.4–5.88]), HGS right (HR 4.44; 95% CI [1.79–10.98]), functional reach (HR 3.69; 95% CI [1.82–7.48]), isometric quadriceps strength right (HR 2.86; 95% CI [1.43–5.72]), 30s-STS (HR 3.44; 95% CI [1.66–7.11]). Conclusion Baseline walking distance, muscular strength and endurance in the legs were independently associated with survival in people with CKD stages 3–5 without KRT. After completing 12 months of exercise training improved walking distance, muscular strength and endurance, and balance were positively associated with survival, compared with noncompleters. Better physical performance at baseline and the ability to complete 12 months of exercise training conferred survival benefits. There are probably several factors affecting better survival. These factors require elucidation in future studies. Trial registration ClinicalTrials.gov NCT02041156. Registration date 20,240,107.